2020
DOI: 10.1002/jat.4092
|View full text |Cite
|
Sign up to set email alerts
|

Linking emerging contaminants exposure to adverse health effects: Crosstalk between epigenome and environment

Abstract: Environmental epigenetic findings shed new light on the roles of epigenetic regulations in environmental exposure‐induced toxicities or disease susceptibilities. Currently, environmental emerging contaminants (ECs) are in focus for further investigation due to the evidence of human exposure in addition to their environmental occurrences. However, the adverse effects of these environmental ECs on health through epigenetic mechanisms are still poorly addressed in many aspects. This review discusses the epigeneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 147 publications
(216 reference statements)
0
7
0
Order By: Relevance
“…It should be noted that the higher concentration of Al (<0.5 mg/L), Fe (<1.0 mg/L), Cu (<1 mg/L), Mg (<200 mg/L), and Zn (<5 mg/L) in the aquatic ecosystem and groundwater are potentially harmful to the human health [ 72 ] and have a prolonged association with various diseases such as cardiovascular disease (CD), cancer, Alzheimer disease (AD), Huntington disease (HD), diabetes mellitus (DM), Parkinson disease (PD), etc. [ 73 , 74 , 75 ]. Currently, various classes of antibiotics are frequently entering the environment through/via wastewater treatment plants (WWTPs), hospital wastewater, the pharmaceutical industry, and landfills [ 76 ], massively polluting the overall environment.…”
Section: Emerging Contaminants (Ecs) In Msw Landfillsmentioning
confidence: 99%
“…It should be noted that the higher concentration of Al (<0.5 mg/L), Fe (<1.0 mg/L), Cu (<1 mg/L), Mg (<200 mg/L), and Zn (<5 mg/L) in the aquatic ecosystem and groundwater are potentially harmful to the human health [ 72 ] and have a prolonged association with various diseases such as cardiovascular disease (CD), cancer, Alzheimer disease (AD), Huntington disease (HD), diabetes mellitus (DM), Parkinson disease (PD), etc. [ 73 , 74 , 75 ]. Currently, various classes of antibiotics are frequently entering the environment through/via wastewater treatment plants (WWTPs), hospital wastewater, the pharmaceutical industry, and landfills [ 76 ], massively polluting the overall environment.…”
Section: Emerging Contaminants (Ecs) In Msw Landfillsmentioning
confidence: 99%
“…Exposure to PM, from coarse PM 10 particles to nanoparticles has been associated with altered DNA methylation in vitro, in vivo, and in humans [39][40][41]. Therefore, epigenetic alterations associated with environmental exposures receive much attention as key mechanisms in the pathogenesis of exposure-associated diseases [42,43]. The first studies to recognize the role of climate change (i.e., heat) and associated epigenetic alterations in the pathogenesis of allergic and respiratory diseases have recently emerged [44].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, exposure to environmental arsenic is prominently related to hypomethylation in blood DNA [ 80 ]. Using a similar approach, another study showed that environmental Pb significantly decreased LINE-1 promoter gene methylation, which resulted in pathological consequences in workers from a battery plant [ 81 ]. Furthermore, tetranitromethane (TNM) exposure has been shown to cause reduced global DNA methylation while increasing ROS and malondialdehyde (MDA) [ 82 ].…”
Section: Relationship Between Epigenetics and Oxidative Stress In The...mentioning
confidence: 99%